Schwannoma Of Lateral Sural Cutaneous Nerve: A Rare Case - Dudhani, Nikhil; Patel, Mrunal; Krishna Vittal Varma, Manthena Rama (Journal of Neonatal Surgery, 2025)
INTRODUCTION: Peripheral nerve sheath tumors (PNSTs) are extremely uncommon, with most of these tumors being benign. Schwannomas, which are benign tumors of the peripheral nerve sheath, are made up entirely of Schwann cells. AIM AND OBJECTIVE: To study about the rare finding of schwannoma of the lateral sural nerve in a patient that presented with pain and localized swelling over the right ankle MATERIAL AND METHODS: A 51-year-old female patient presented with complains of pain over right ankle to the orthopedic specialist clinic of Krishna Hospital, Karad. Examination and investigations revealed a painful mass surrounding the sural nerve. MRI diagnosed it to be a sural nerve tumor. Surgical excision followed by histopathological study confirmed the diagnosis. The following case report discusses this patient’s presentation along with information about schwannomas and their frequency in the lower limb, recommendations for investigation and management. RESULTS: Solitary schwannoma arising from the lateral sural nerve is an extreemely rare finding. The most common complain associated with the tumour is that it presents as a palpable, painful mass over the posterolateral aspect of the ankle and the and associated neurological symptoms usually occuring due to compression of the nerve or the surrounding structures. CONCLUSION: Hence, clinicians must consider schwannoma as a possible diagnosis for a well defined, oval, subcutaneous mass in the posterior aspect of the lower leg and should approach it with discretion for diagnosis of swellings in these areas.